THE FIRST EXPERIENCE OF CLINICAL APPLICATION AUTOLOGICAL MEZENCHIMAL BONE MARROW STEM CELLS FOR REHABILITATION OF RETRACTIVE MYOCARDIAL FUNCTION - V. I. Shumakov; E. N. Kazakov; N. A. Onischenko; S. V. Gureev; E. N. Ostroumov; V. V. Chestuhin; M. E. Krasheninnikov; B. L. Mironkov; A. Sh. Houbutia (Российский кардиологический журнал, 2003)
The previouse experimental studies revealed that mezenchimal bone marrow stem cells (MSC) have the ability of differentiating into cardiomiocytes in vitro and in vivo inducting angiogenesis and restoring the impared myocardial function. At that, the cell technology capacities in clinical cardiology remain unstudied.Starting from January 2003 8 patients suffering from heart failure underwent the transplantation of autological MSC with different stages of cultivation: MSC was administered intracoronary to 6 and intramuraly to the post-infarction cardiosclerosis zone. In three cases the MSC were marked with thallium-20 Idirectly before transplantation in order to define the location of MSC during the hours after transplantation. The results of radionuclide scintigraphy demonstrated that in 1, 5 hours after intracoronary administration and in 6, 5 hours after intramyocardial injection MSC remain in the zone of administration. In 1 month after the transplantation the improvement of regional perfusion and diastolic function was observed in old patients. Significant growth of functional ischemia of the left ventricle from 31 to 40 % was observed in patient suffering from ИКМП after intramural administration of MSC. In 1 month after MSC transplantation quality of life and phisical stress tolerance improvement was observed. Intracoronary administered MSC remain in coronary artery, through which MSC was administered. Intracoronary and intramural administration of MSC improves functional indices of retractive myocardial function, increases physical stress tolerance and life quality of patients suffering from chronic heart failure.